If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2t + 3) = -10 Reorder the terms: -2(3 + 2t) = -10 (3 * -2 + 2t * -2) = -10 (-6 + -4t) = -10 Solving -6 + -4t = -10 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -4t = -10 + 6 Combine like terms: -6 + 6 = 0 0 + -4t = -10 + 6 -4t = -10 + 6 Combine like terms: -10 + 6 = -4 -4t = -4 Divide each side by '-4'. t = 1 Simplifying t = 1
| X+3+4x-1=27 | | 2(10-n)=n+50 | | 39F-40=-27 | | 180=(11x-40)+59 | | 10d^2-3d=0 | | 10(s-4)=-124 | | -9n+4=-2n+24 | | -(c-8)=6 | | -(c-8)=-124 | | -21+a=30 | | 5v^2-31v-28=0 | | 9n+3=5 | | 35x+80=24-90x | | y^2=x+4 | | 2v+7=1 | | 3(4s+7)=129 | | -2=x-(-5) | | 12x-30=4x-6 | | 2x-5y=42 | | 8y-8=4y-3 | | 6(2l+10)=192 | | C-(-3)=8 | | y=-4/9x-3=-7/5x-3 | | 2(a-8)=16 | | 9x-3Y=x+y | | x^2+1.8x-0.1516=0 | | 2n=36+-44 | | (q-8)*2=10 | | 3x+7=-7+2x | | 21=n+21 | | 5x+3x=7x+2x | | 5/6n=10 |